Qualidade física, fisiológica e sanitária de sementes de feijão-caupi armazenadas com pó folhas de plantas da caatinga - Diógenes, Francisco ésio Porto (2014)
Vigna unguiculata (L.) Walp., known as cowpea beans, is a perishable goods exposed to damages in relatively short time conservation periods, especially in traditional storage system or silo. This work had as its objective to verify physical, physiological and sanitary quality of cowpea beans seeds stored, during 150 days, with juazeiro leaf powder (Ziziphus joazeiro Mart.), jucá (Caesalpinia ferrea Mart.) and mulungu (Erythrina velutina Willd.). Experiments were accomplished Laboratório de Análise Sementes da Universidade Federal do Semi-Árido (UFERSA), Mossoró, RN, from April to September 2013. Cultivars BRS Marataoã e BRS Potiguar, whose seeds were stored in polyethylene bottles, during 150 days, containing leaves powder originated from forest species of Caatinga on the ratio of 10 g kg-1 seed. Statistical design was completely randomized in factorial scheme 4 x 5, consisting of four treatments (control, juazeiro leaf powder, jucá and mulungu) and five storage times (30, 60, 90, 120 and 150 days). The seeds were submitted to the following tests: humidity level, hectoliters weight, one thousand seeds weight, assessment of seeds infested by insects, germination test, emergence speed index, accelerated ageing, electrical conductivity and sanity test. The averages were compared by Scott-Knot test, at 5% probability, analyzed through statistical program SISVAR and fit to regression lines. The powders with leaves of juazeiro, jucá and mulungu did not affect germination and seeds vigor stored during 150 days. Powders of juazeiro and mulungu leaves tended to reduce the infestation of seeds by insects during storage. The use of mulungu leaves powder in ratio10 g kg-1 made it possible low Rhizopus sp. fungal rate in cowpea beans, cultivaras cultivares BRS Marataoã and BRS Potiguar, during 150 days of seeds storage